TLR4/AP-1-Targeted Anti-Inflammatory Intervention Attenuates Insulin Sensitivity and Liver Steatosis - Xiang Hu; Jing Zhou; Sha-sha Song; Wen Kong; Yan-Chuan Shi; Lu-Lu Chen; Tian-Shu Zeng (Mediators of Inflammation)
Insulin resistance has been shown to be the common pathogenesis of many metabolic diseases. Metainflammation is one of the important characteristics of insulin resistance. Macrophage polarization mediates the production and development of metainflammation. Toll-like receptor 4 (TLR4) mediates macrophage activity and is probably the intersection of immunity and metabolism, but the detailed mechanism is probably not fully understood. Activated protein 1 (AP1) signaling pathway is very important in macrophage activation-mediated inflammation. However, it is unclear whether AP1 signaling pathway mediates metabolic inflammation in the liver. We aimed to investigate the effects of macrophage TLR4-AP1 signaling pathway on hepatocyte metabolic inflammation, insulin sensitivity, and lipid deposition, as well as to explore the potential of TLR4-AP1 as new intervention targets of insulin resistance and liver steatosis. TLR4 and AP1 were silenced in the RAW264.7 cells by lentiviral siRNA transfection. In vivo transduction of lentivirus was administered in mice fed with high-fat diet. Insulin sensitivity and inflammation were evaluated in the treated cells or animals. Our results indicated that TLR4/AP-1 siRNA transfection alleviated high-fat diet-induced systemic and hepatic inflammation, obesity, and insulin resistance in mice. Additionally, TLR4/AP-1 siRNA transfection mitigated palmitic acid- (PA-) induced inflammation in RAW264.7 cells and metabolic abnormalities in cocultured AML hepatocytes. Herein, we propose that TLR4-AP1 signaling pathway activation plays a crucial role in high fat- or PA-induced metabolic inflammation and insulin resistance in hepatocytes. Intervention of the TLR4 expression regulates macrophage polarization and metabolic inflammation and further alleviates insulin resistance and lipid deposition in hepatocytes.